EFEKTIVITAS PENERAPAN MODEL INDUKTIF KATA BERGAMBAR DAN‏ ‏‏INVESTIGASI KELOMPOK TERHADAP HASIL BELAJAR KITABAH ‎ SISWA ‎SEKOLAH DASAR - Afifurrahman, Muhammad; Erlina, Erlina; Ghazi, Fachrul; Koderi, Koderi; Sufian, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes in Kitabah and the teacher-centered learning approach, which made students passive in the learning process. The research aims to examine the effectiveness of the Inductive Pictured Words Model and the Group Investigation Model on Kitabah learning outcomes among elementary school students. This study employs a quantitative approach with an experimental method, specifically using a quasi-experimental design with a pretest-posttest control group design. The sample was selected through cluster random sampling and consisted of sixth-grade students at SD Al Azhar Bandar Lampung, with 28 students in the experimental class and 25 students in the control class. The research findings indicate that the Inductive Pictured Words Model and the Group Investigation Model significantly improve students' Kitabah learning outcomes. The t-test results show that t-value (3.506) exceeds t-table (2.005), leading to the acceptance of H₁, which confirms that these models positively impact students' learning achievements. Posttest data reveal that the experimental class obtained an average learning outcome score of 81.20, while the control class scored 72.1. Additionally, these models foster scientific attitudes, with the highest score recorded in objectivity/honesty (83.57%) and the lowest in collaboration (68.57%). Overall, the findings suggest that the Inductive Pictured Words Model and the Group Investigation Model are effective learning strategies that enhance Kitabah learning outcomes and scientific attitudes, making them suitable for use in elementary school education.